Iron complexes: green and sustainable synthesis and evaluation of their potency as antioxidants and inhibitors of DNA damage in rats - Fayze Mohamed Eissa; Heba Abdelaziz; Abdelsalam Arfein; Zeinab Mohamed (Acta Scientiarum. Biological Sciences, 2024)
Three iron complexes were synthesized through green and sustainable procedures via chelation with salicylic acid, 3-methyl-1-phenyl-pyrazol-5-one, and ethylacetoactate under solvent-free conditions at room temperature. The synthesis assured the concept of both the twelve principles of Green Chemistry and Sustainability Commands. 48 male Wistar albino rats were administered gentamicin (GM) at a dose of 80 mg kg-1 day-1, with or without (I-SA), (I-MPP), (I-EAA) (120 mg kg-1 day-1) to evaluate the complexes' potential protective effects against GM-induced hepatotoxicity and nephrotoxicity. Oxidative stress markers and DNA fragmentation increased significantly, while the activity of the antioxidant enzymes SOD and CAT notably decreased. The study findings suggest that the three complexes serve as novel natural antioxidants, mitigating oxygen free radicals, lipid peroxidation, and DNA damage in gentamicin-treated rats. These compounds hold promise as potential natural drugs in future applications.